MODEL PEMBELAJARAN MENYENANGKAN DAN EFEKTIF DENGAN PENGGUNAAN GAME PENDIDIKAN AGAMA ISLAM PADA MASA PTMT - Rizal Dalil; Annur Safarnaa (MGMP PAI Jawa Barat, 2022)
The outraging of COVID-19 pandemic for this nearly two years has had a profound impact on the education section. Based on the problem above, the Ministry of Education issued a limited Face-to-Face Learning (PTMT) policy during the pandemic to prevent learning loss. Ironically, there are still many students who often do not take lessons due to a lack of motivation as a result of the pandemic. This lack of learning motivation will certainly affect student's achievement greatly. Therefore, the authors feel challenged to design a fun and effective learning model during the PTMT period by using learning games which are expected to increase students' motivation and learning achievement in learning Islamic Religion and Character Education (PAI and BP). Best practice in class VII-E of SMPN 1 Bogor City is implemented with a hybrid learning model, which is conducting offline and online teaching at the same time. Based on the results of this study, it can be concluded that there is a significant positive effect between the use of PAI and BP games on students' motivation and learning achievement. The results of this study are expected to be an inspiration for teachers to be more creative and innovative so that PAI and BP learning will be more fun and effective.